2002
DOI: 10.1128/cdli.9.3.725-726.2002
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of Additional Anticapsular Antibody Concentrations to the Neisseria meningitidis Group A, C, Y, and W-135 Meningococcal Standard Reference Serum CDC1992

Abstract: We assigned additional enzyme-linked immunosorbent assay antibody concentrations (immunoglobulin G [IgG], IgM, and IgA, and total) to the Neisseria meningitidis standard reference serum CDC1992 for groups Y and W-135 to 12 Centers for Disease Control and Prevention quality control sera. These assignments will supplement previous assignments and will aid in the evaluation of present and developing vaccines.Meningococcal vaccine evaluation requires the use of quantitative and functional antibody determinations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Standard human reference serum CDC1992 (National Institute of Biological Standards and Control [NIBSC] code 99/706, pooled sera from 14 adults vaccinated with a meningococcal A, C, W, and Y polysaccharide vaccine) was obtained from NIBSC, and the serogroup-specific concentrations of IgG and IgA antibodies previously assigned to it were used for quantification of samples (20,21). To develop and evaluate the assay, a control panel of 15 serum and 15 saliva samples were established.…”
Section: Methodsmentioning
confidence: 99%
“…Standard human reference serum CDC1992 (National Institute of Biological Standards and Control [NIBSC] code 99/706, pooled sera from 14 adults vaccinated with a meningococcal A, C, W, and Y polysaccharide vaccine) was obtained from NIBSC, and the serogroup-specific concentrations of IgG and IgA antibodies previously assigned to it were used for quantification of samples (20,21). To develop and evaluate the assay, a control panel of 15 serum and 15 saliva samples were established.…”
Section: Methodsmentioning
confidence: 99%
“…Data abstraction and analysis were performed using MasterPlex CT/QT software (MiraiBio Inc., San Francisco, CA, USA). The concentration of meningococcal serogroup-specific IgG in test sera was calculated relative to the human standard reference serum CDC1992 (20).…”
Section: Seramentioning
confidence: 99%
“…These assays use a standard reference serum, such as CDC1992, to calculate IgG concentrations in micrograms per milliliter ([IgG]g/ml) in unknown samples. Anti-MnPS immunoglobulin concentrations have been assigned to CDC1992 by cross-standardization in studies reported elsewhere (9,13,15). Previously, we showed that for ELISA procedures involving Y and W135 MnPS antigens, the optimal assay plate coating concentrations are serum specific (10), and therefore, interlaboratory agreement may be influenced by antigen coating concentration.…”
mentioning
confidence: 99%
“…The published protocol for the meningococcal ELISA was used with minor modifications to measure MnPS serogroup-specific concentrations of IgG antibodies in unknown subject sera and control sera using the reference standard CDC1992 (9,13 SBA. Functional bactericidal antibodies were assessed in sera as previously described (7,22,31).…”
mentioning
confidence: 99%